COVID-19 pandemic accelerated virtual transformation in dental education: a multicenter review of remote teaching and teledentistry - Constanza E. FERNÁNDEZ; Eder A. SIGUA-RODRIGUEZ; Clara I. VERGARA-HERNÁNDEZ; Victor H. TORAL-RIZO; Gustavo TELLO; Cristhian C. MADRID TROCONIS; Sthefanie PEREZ PUELLO; Gina D. ROQUE-TORRES (RGO: Revista Gaúcha de Odontologia, 2021)
ABSTRACT Although prior to the pandemic there was some resistance to the virtualization of dental education, the COVID-19 pandemic is providing us a unique opportunity to overcome several barriers that previously blocked the adoption of remote teaching and teledentistry. Thanks to the extended availability of telecommunications, digital technologies, and platforms, remote education and teledentistry appear to be the preferred choice to maintain dental education and patient care active under this pandemic, without contamination risks. In this paper, we review valid remote education strategies and possible alternatives useful in virtual transformation in dental education. Furthermore, the role of teledentistry and its advantages and challenges are also revised. Under the current pandemic context, as dental educators, we are called to be creative and flexible. Every dental school should adapt and use remote education as much as possible until clinical attention can be readopted. The evidence presented in this review supports our position that under this pandemic, remote education and telemedicine/teledentistry may be “the virtual convenient solution”, to adapt and improve the hitherto classic way of teaching dentistry through tele-education.